Isolation and Characterization of Cold-Tolerant Hyper-ACC-Degrading Bacteria from the Rhizosphere, Endosphere, and Phyllosphere of Antarctic Vascular Plants - Macarena A. Araya; Tamara Valenzuela; Nitza G. Inostroza; Fumito Maruyama; Milko A. Jorquera; Jacquelinne J. Acuña (Microorganisms, 2020)
1-Aminociclopropane-1-carboxylate (ACC)-degrading bacteria having been widely studied for their use in alleviating abiotic stresses in plants. In the present study, we isolated and characterized ACC-degrading bacteria from the rhizosphere, phyllosphere, and endosphere of the Antarctic vascular plants Deschampsia antarctica and Colobanthus quitensis. One hundred and eighty of the 578 isolates (31%) were able to grow on minimal medium containing ACC, with 101 isolates (23, 37, and 41 endosphere-, phyllosphere- and rhizosphere-associated isolates, respectively) identified as being genetically unique by enterobacterial repetitive intergenic consensus (ERIC)-PCR. Subsequently, freeze/thaw treatments and ice-recrystallization-inhibition (IRI) activity assays were performed, the results of which revealed that 77 (13%) of cold-tolerant isolates exhibited putative ACC deaminase activity. Significant (p ≤ 0.05) differences in IRI activity were also observed between the studied plant niches. Surprisingly, all the cold-tolerant isolates showed ACC deaminase activity, independent of the plant niches, with 12 isolates showing the highest ACC deaminase activities of 13.21–39.56 mmol α KB mg protein−1 h−1. These isolates were categorized as ‘cold-tolerant hyper-ACC-degrading bacteria’, and identified as members of Pseudomonas, Serratia, and Staphylococcus genera. The results revealed the occurrence of cold-tolerant hyper-ACC-degrading bacteria in diverse plant niches of Antarctic vascular plants, that could be investigated as novel microbial inoculants to alleviate abiotic stresses in plants.